The role of nanoparticles in plant biochemical, physiological, and molecular responses under drought stress: A review - Rasheed, Adnan; Li, Huijie; Tahir, Majid M.; Mahmood, Athar; Nawaz, Muhammad; Shah, Adnan Noor; Aslam, Muhammad Talha; Negm, Sally; Moustafa, Mahmoud; Hassan, Muhammad Umair; Wu, Ziming (Frontiers in Plant Science, 2022)
Drought stress (DS) is a serious challenge for sustaining global crop production and food security. Nanoparticles (NPs) have emerged as an excellent tool to enhance crop production under current rapid climate change and increasing drought intensity. DS negatively affects plant growth, physiological and metabolic processes, and disturbs cellular membranes, nutrient and water uptake, photosynthetic apparatus, and antioxidant activities. The application of NPs protects the membranes, maintains water relationship, and enhances nutrient and water uptake, leading to an appreciable increase in plant growth under DS. NPs protect the photosynthetic apparatus and improve photosynthetic efficiency, accumulation of osmolytes, hormones, and phenolics, antioxidant activities, and gene expression, thus providing better resistance to plants against DS. In this review, we discuss the role of different metal-based NPs to mitigate DS in plants. We also highlighted various research gaps that should be filled in future research studies. This detailed review will be an excellent source of information for future researchers to adopt nanotechnology as an eco-friendly technique to improve drought tolerance.